2018
DOI: 10.1088/2058-6272/aab302
|View full text |Cite
|
Sign up to set email alerts
|

Control of multidrug-resistant planktonicAcinetobacter baumannii: biocidal efficacy study by atmospheric-pressure air plasma

Abstract: In this research, an atmospheric-pressure air plasma is used to inactivate the multidrug-resistant Acinetobacter baumannii in liquid. The efficacy of the air plasma on bacterial deactivation and the cytobiological variations after the plasma treatment are investigated. According to colony forming units, nearly all the bacteria (6-log) are inactivated after 10 min of air plasma treatment. However, 7% of the bacteria enter a viable but non-culturable state detected by the resazurin based assay during the same pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 57 publications
(64 reference statements)
1
9
0
Order By: Relevance
“…While the pure helium gas NTP was only less effective, the helium/air mixture gas NTP led to the full inactivation of A. baumannii (7 log decrease). A complete inactivation of A. baumannii was also reported by Ruan et al (2018) , who used the NTP in open air. A rapid decrease of the surviving bacteria was observed in 2 ml suspension of 10 6 CFU/ml concentration after 5 min of NTP exposure; a total inactivation occurred after 10 min.…”
Section: Non-thermal Plasma Treatment Of Eskape Pathogenssupporting
confidence: 53%
“…While the pure helium gas NTP was only less effective, the helium/air mixture gas NTP led to the full inactivation of A. baumannii (7 log decrease). A complete inactivation of A. baumannii was also reported by Ruan et al (2018) , who used the NTP in open air. A rapid decrease of the surviving bacteria was observed in 2 ml suspension of 10 6 CFU/ml concentration after 5 min of NTP exposure; a total inactivation occurred after 10 min.…”
Section: Non-thermal Plasma Treatment Of Eskape Pathogenssupporting
confidence: 53%
“…The air plasma discharge electrode consists of six copper rods with a diameter of 1 mm. Other articles have reported similar types of configuration (24,25). In the present study, the six electrodes were driven by high voltage direct current (DC) without the requirement for any external gas supply.…”
Section: Preparation Of Plasma-activated Solutionmentioning
confidence: 84%
“…An analysis of PAL revealed that its major components are ROS and reactive nitrogen species (RNS), which can effectively inactivate various bacteria [16]…”
Section: Discussionmentioning
confidence: 99%
“…The intracellular ROS concentration was evaluated using a ROS assay kit (Beyotime, China)[ 16 ]. After immersing the bacterial cells in PAL for 30 min, the bacterial suspension was mixed with diluted 2,7-dichlorodihydrofluorescein diacetate (DCFH-DA) solution and incubated for 20 min at 37°C in the dark.…”
Section: Methodsmentioning
confidence: 99%